Relationship Between Interleukin-6 −174G/C Genetic Variant and Efficacy of Methotrexate Treatment in Psoriatic Arthritis Patients - Sokolik R; Iwaszko M; Świerkot J; Wysoczańska B; Korman L; Wiland P; Bogunia-Kubik K (Dove Medical Press, 2021)
Renata Sokolik,1,* Milena Iwaszko,2,* Jerzy Świerkot,1 Barbara Wysoczańska,2 Lucyna Korman,1 Piotr Wiland,1 Katarzyna Bogunia-Kubik2 1Department of Rheumatology and Internal Medicine, Wrocław Medical University, Wrocław, Poland; 2Laboratory of Clinical Immunogenetics and Pharmacogenetics, Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wrocław, Poland*These authors contributed equally to this workCorrespondence: Milena IwaszkoHirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Weigla 12, Wrocław 53-114, PolandTel +48 71 3709960Fax +48 71 3371382Email milena.iwaszko@hirszfeld.plIntroduction: The purpose of the study was to investigate whether single-nucleotide polymorphisms (SNPs) IL-6 − 174 G/C and IL-6R Asp358Ala are associated with susceptibility to psoriatic arthritis (PsA) or affect response to treatment with methotrexate (MTX).Patients and Methods: Seventy-four patients diagnosed with PsA and qualified for MTX treatment were enrolled to the study. The control group consisted of 120 healthy individuals. Polymorphisms IL-6 − 174 G/C and IL-6R Asp358Ala were genotyped using a polymerase chain reaction (PCR) amplification employing LightSNiP assays.Results: A significant association between the IL-6 − 174 CC genotype and an improved clinical outcome of MTX therapy was observed. A good response was more frequently observed among PsA patients bearing the IL-6 − 174 CC genotype than patients with the GC or GG genotypes (P = 0.007). On the other hand, patients carrying the IL-6 − 174 GC genotype less frequently responded to MTX treatment as compared to patients with other genotypes (P = 0.006). With respect to the IL-6R Asp358Ala SNP, there were no significant differences in genotype and allelic frequencies in relation to clinical outcome of MTX treatment. No association was found between the IL-6 − 174 G/C or IL-6R Asp358Ala SNPs and PsA susceptibility.Conclusion: Results from this study provide evidence that the IL-6 − 174 G/C polymorphism might influence efficacy of MTX treatment.Keywords: psoriatic arthritis, methotrexate treatment, IL-6 − 174G/C polymorphism, IL-6R Asp358Ala polymorphism